Megaesôfago secundário a anomalia do anel vascular e luxação de patela em um cão. - Silva, Ana Caroline Alves da (Universidade Federal do Tocantins, 2023)
The purpose of this report is to describe the activities carried out during the Supervised Curricular Internship, fully held in the Veterinary Hospital of the Federal University of Piauí, from March 13th to May 26th, 2017, totalizing 400 hours. The activities developed were in the area of Medical and Surgical Clinic of small animals under the guidance of Professor Dr. Tiago Barbalho Lima and under the local supervision of the Veterinary resident Andressa Kelly Barbosa Rufino. During the internship period, 179 medical clinic cases and 81 surgical procedures were followed in the small animal sector of the hospital. This work includes the activities carried out during the internship period, which include assistance to residents in performing ambulatory, surgical and emergency procedures, and monitoring and evolution of patients within the hospitalization unit. The data related to the technical activities developed and to the cases followed are organized in the form of tables and graphs. A case of a dog presenting megaesophagus secondary to a vascular ring anomaly (possible persistence of the fourth right aortic arch) associated with lateral patellar luxation will also be reported and discussed. The recommended clinical management for the first condition involved feeding in an erect position; however, its application was not possible due to the presence of the patellar luxation, making its surgical correction indispensable for the correct treatment of the conditions.